Development of a Diagnostic Clinical Score for Hemodynamically Significant Patent Ductus Arteriosus - Annemarie Kindler; Barbara Seipolt; Antje Heilmann; Ursula Range; Mario Rüdiger; Sigrun Ruth Hofmann (Frontiers Media S.A., 2017)
There is no consensus about the hemodynamic significance and, therefore, the need to treat a persistent ductus arteriosus in preterm newborns. Since the diagnosis of a hemodynamically significant persistent ductus arteriosus (hsPDA) is made by a summary of non-uniform echo-criteria in combination with the clinical deterioration of the preterm neonate, standardized clinical and ultrasound scoring systems are needed. The objective of this study was the development of a clinical score for the detection and follow-up of hsPDA. In this observational cohort study of 154 preterm neonates (mean gestational age 28.1 weeks), clinical signs for the development of hsPDA were recorded in a standardized score and compared to echocardiography. Analyzing the significance of single score parameters compared to the diagnosis by echocardiography, we developed a short clinical score (calculated sensitivity 84% and specificity 80%). In conclusion, this clinical diagnostic PDA score is non-invasive and quickly to implement. The continuous assessment of defined clinical parameters allows for a more precise diagnosis of hemodynamic significance of PDA and, therefore, should help to detect preterm neonates needing PDA-treatment. The score, therefore, allows a more targeted use of echocardiography in these very fragile preterm neonates.